Diane PECORARI. Teaching to Avoid Plagiarism. How to Promote Good Source Use,Berkshire, England: Open University Press. McGraw-Hill Education, 2013, xiii + 192 pp.ISBN 13: 978-0-33-524593-2 (pb)ISBN 10: 0-33-524593-5 (pb)eISBN: 978-0-33-524594-9 - Pinto, Maria da Graça Lisboa Castro (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.